The Portrayal of Serial Killers in Thomas Harris’ Novel Read Dragon - Sallal, Omar (Al-Adab Journal, 2023)
This study aims to deeply analyze the character of serial killers in Thomas Harris’ novels and focuses on his novel Red Dragon. The Study searches in these complex and deep characters through the use of Erich Fromm's concepts about the destructive nature of the human psyche and what are the factors affecting serial killers in all social psychological, and biological aspects. This study Concluded: Thomas Harris portrayed the characters of serial killers in a professional and complex and made the reader go on a contemplative journey in the mind and soul of the serial killer, thus reaching the climax of artistic perfection.